Efficient Wireless Vibration Data Sensing and Signal Processing Technique Based on the Android Platform - Chan-Seob Park; Ryong Baek; Woong Hoe; Byung-Gyu Kim; Hyun-Jun Lee (International Journal of Distributed Sensor Networks, 2014)
Recently, many researches on big-data sensing and analysis have been actively promoted. The big data, which is generated by the digital and networked environment, is referred to to form not only numerical data, but also large-scale data for storing image data and character. Usually, many data measured through sensors are very large in scale in various vibration measurements. Measurement methods for vibration analysis currently consist of a general sensing scheme using cabling to obtain vibration data. The system is difficult to use efficiently in a location where equipment installation is not easy. We proposed a novel vibration measurement system that includes a main hardware module and a wireless data transceiver module. The system is easy to use and field data are transmitted to a remote location using Bluetooth communication and the Android platform. Nonexpert personnel can obtain field vibration data for transport, even over long distances. Through experiments in field test, we verify that the stable remote sensing range reaches up to 150 m in real-time communication without any data loss.